Lexical borrowing from the Arabic language in an Islamic course conducted in English - Arshad, Nurul-Ikhlas; Ahamad Shah, Mohamed Ismail (IDOSI Publications, 2014)
This study analysed the patterns and processes of borrowing that can occur in the retention of Islamic Arabic words. This research revealed that the most common process of borrowing in the sample discourse is total importation, as loanwords make up the majority of the borrowed features. Recommendations are provided in this aspect, particularly in teaching Islamic Studies in the English language as well as in retaining Islamic Arabic terms in the general discourse among Muslims.